Rancang Bangun Kontrol Spreader Berbasis Android Menggunakan Arduino Mega 2560 di Kapal Floating - Muh. Nasrul; Agus Dwi Santoso; Teguh Pribadi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The shipping industry is closely related to economic growth in various countries. This transportation is very dependent on export and import activities. As the country's economy improves, especially in Asia, the maritime transportation business in Indonesia will also develop. The pattern of sending goods via sea transportation has changed, especially in terms of bulk transportation. which demands modern technology such as automation and intelligent control systems. This research aims to design and develop Android-based spreader control using Arduino Mega 2560 on a floating ship. This project is designed to increase efficiency and ease of operation in the loading and unloading process on ships, which previously still used manual control with a remote control or joystick which had limitations such as limited visibility. In this research, the spreader control system is connected to an Arduino Mega 2560 microcontroller via the HC-05 Bluetooth module, allowing the operator to control the spreader via an Android device. Test results show that data is obtained at a distance of 1 to 13 meters, the Android-based spreader control system shows a response time ranging from 1 to 9 seconds, which shows that the system is functioning properly. At a distance of 14 to 19 meters, the response time increases to 18 seconds, indicating quite good system performance. This shows that there is quite significant latency in data transmission. However, the system still managed to carry out spreader control well. At 20 meters, the system failed to respond to the spreader control. This shows that the effective range of this Bluetooth module is below 15 meters. This research makes a significant contribution to the development of automatic control technology in the shipping industry, especially in the use of intelligent control systems integrated with mobile devices.